The Influence of Remuneration on Employee Productivity levels: A Case Study of Darling Uganda Limited - Ruth Atuhaire (Uganda Christian University, 2023)
The study examined the influence of remuneration on employee productivity levels and used a case study of darling Uganda limited employees 2023. The major research gap under investigation was mainly the limited productivity of employees that is attributed to demotivation from employers especially In terms of unfavourable remuneration strategies, and thus, what is causing poor remuneration standards at darling factory? In order to effectively answer the highlighted research problem, the researcher employed the case study research design to examine the data about the influence of remuneration on employee productivity. The case study research design was used as the most suitable research design mainly because the researcher needed adequate details about the problem of study and the time frame was limited. In so doing, the researcher focused on the Darling factory employees as a specific case for the study and from which, generalisation about the findings of the case study would be made. The research established that lack of job security in the private sector, low payments, bad payment schedule and the lack of equity between the amount of work done and payment were the major bottlenecks that affected remuneration and thus resulted into low employee productivity. Therefore, it was concluded that employee productivity and compensation have a significant relationship. That is to say, based on the findings of this study, compensation has a direct effect on overall employee productivity. In doing so, some of the remuneration gaps that needed to be addressed by employers included: a lack of employee motivation due to the absence of fringe and performance benefits; a lack of team building; a lack of job security; a poor payment schedule; and lower salaries paid to the employees. Therefore, the study provided important recommendations that included; provision of on board training to employees, remuneration adjustment and improvement on the job security especially in the private sector of Uganda.
This is a dissertation.